Computer and fuzzy theory application: review in home appliances - Tim Chen; Ilnar Karimov; Jcy Chen; Alexandv Constantinovitc (Journal of Fuzzy Extension and Applications, 2020)
Clays have a tendency to this article first introduces the basic concepts of fuzzy theory, including comparisons between fuzzy sets and traditional explicit sets, fuzzy sets basic operations such as the membership function of the set and the colloquial variable, the intersection and union of the fuzzy set, and use the above concepts to guide into the four basic reasoning mechanisms of fuzzy mode and introduce several common types of fuzzy application examples such as fuzzy washing machine and fuzzy control of incinerator plant in China illustrate the application of fuzzy theory in real society.